Peritoneal dialysis as therapeutic option in heart failure patients - Grossekettler, Leonie; Schmack, Bastian; Kreußer, Michael; Frankenstein, Lutz; Kihm, Lars Philipp; Zeier, Martin; Katus, Hugo; Schwenger, Vedat (ESC heart failure, 2019)
Aims: Each episode of acute decompensated heart failure (HF) incrementally adds to mortality. Peritoneal dialysis (PD) offers an alternative therapeutic option in refractory HF and reduces the incidence of decompensation episodes. The objective of this study was to determine the efficacy of PD, in terms of functional status, surrogate endpoints, rate of hospitalizations, and mortality. Methods and results: This study is based on the registry of the German Society of Nephrology, involving 159 patients receiving PD treatment due to refractory HF between January 2010 and December 2014. Body weight was reduced by PD (82.2 ± 14.9 to 78.4 ± 14.8 kg, P < 0.001), and significant improvements in New York Heart Association functional class (3.38 ± 0.55 to 2.85 ± 0.49, P < 0.001) were found already after 3 months. Left ventricular ejection fraction did not change (31.5 ± 13.8 to 34.0 ± 15.7%, P = 0.175). C-reactive protein improved with PD treatment (33.7 ± 52.6 to 17.1 ± 26.3 mg/L, P = 0.004). Blood urea nitrogen/creatinine ratio decreased significantly (148.7 ± 68.3 to 106.7 ± 44.8 mg/dL, P < 0.001). Hospitalization rates decreased significantly (total number 2.86 ± 1.88 to 1.90 ± 1.78, P = 0.001, and 39.2 ± 30.7 to 27.1 ± 25.2 days, P = 0.004). One year mortality was 39.6% in end-stage HF patients treated with PD. Conclusions: Peritoneal dialysis offers an additional therapeutic option in end-stage HF and is associated with improved New York Heart Association classification and reduced hospitalization. Although PD treatment was associated with various benefits, further studies are necessary to identify which patients benefit the most from PD.
Gesehen am 21.05.2019